Factors that influence human behavior in fuelwood use and their implications for biocultural conservation - Cruz, Ramon Salgueiro; Medeiros, Patrícia Muniz de; Ferreira Júnior, Washington Soares; Silva, Rafael Ricardo Vasconcelos da (Ethnobiology and Conservation, 2020)
A set of investigations has attempted to identify patterns in human resource use behavior to drive conservation strategies. However, it is still necessary to advance the understanding of the factors that influence human decision making in the use of resources, considering the perceived cost-benefit relationships. In this research, we assessed whether cost-benefit rationale may explain why certain resources are more used than others, as well as the factors that can predict resource consumption by certain families. We adopted the use of biofuels as research model in a rural settlement in northeastern Brazil. Our main findings indicate that the species most frequently used by people are those that favor the cost-benefit relationship. Resource availability was the main variable that directed the frequency of use of the species, and only the number of people in the residences explained the consumption of firewood by the families. These findings can provide important insights for the elaboration of biocultural conservation strategies because they present the mechanisms that can direct the behavior in the use of certain resources and the greater consumption of firewood by certain families.